Delta opioid receptors affect acoustic features of song during vocal learning in zebra finches - Utkarsha A. Singh; Soumya Iyengar (BMC Neuroscience)
Abstract Delta-opioid receptors (δ-ORs) are known to be involved in associative learning and modulating motivational states. We wanted to study if they were also involved in naturally-occurring reinforcement learning behaviors such as vocal learning, using the zebra finch model system. Zebra finches learn to vocalize early in development and song learning in males is affected by factors such as the social environment and internal reward, both of which are modulated by endogenous opioids. Pairs of juvenile male siblings (35-day-old) were systemically administered a δ-OR-selective antagonist naltrindole or vehicle (controls) for a period of 10 days. The acoustic structure of songs differed across treated and control groups at adulthood (120 days). Naltrindole-treated birds had a significantly lower pitch, mean frequency, and frequency modulation than controls, whereas there was no difference in the number of songs in naltrindole-treated and control siblings. Since the opioid and dopaminergic systems interact, we decided to study whether blocking δ-ORs during the sensitive period led to changes in dopaminoceptive neurons in Area X, a song control nucleus in the basal ganglia. Interestingly, compared with controls, naltrindole-treated birds had higher numbers of DARPP-32-positive medium spiny neurons and potentially excitatory synapses in Area X. We show that manipulating δ-OR signaling during the learning phase resulted in alterations in the acoustic features of song and had long term effects on dopaminergic targets within the basal ganglia in adulthood. Our results suggest that endogenous opioids regulate the development of cognitive processes and the underlying neural circuitry during the sensitive period for learning.